SarT, a Repressor of α-Hemolysin in Staphylococcus aureus - Schmidt, Katherine A. (American Society for Microbiology, 2001)
In searching the Staphylococcus aureus genome, we found several homologs to SarA. One of these genes, sarT, codes for a basic protein with 118 residues and a predicted molecular size of 16,096 Da. Northern blot analysis revealed that the expression of sarT was repressed by sarA and agr. An insertion sarT mutant generated in S. aureus RN6390 and 8325-4 backgrounds revealed minimal effect on the expression of sarR and sarA. The RNAIII level was notably increased in the sarT mutant, particularly in postexponential-phase cells, while the augmentative effect on RNAII was less. SarT repressed the expression of α-hemolysin, as determined by Northern blotting, Western blotting, and a rabbit erythrocyte hemolytic assay. This repression was relieved upon complementation. Similar to agr and sarA mutants, which predictably displayed a reduction in hla expression, the agr sarT mutant exhibited a lower level of hla transcription than the sarT mutant. In contrast, hla transcription was enhanced in the sarA sarT mutant compared with the single sarA mutant. Collectively, these results indicated that the sarA locus, contrary to the regulatory action of agr, induced α-hemolysin production by repressing sarT, a repressor of hla transcription.